Relaciones canadiense-latinoamericanas pasadas, presentes y futuras - Ogelsby, J. C. M. (Estudios Internacionales, 1972)
Knowingly or not, the Trudeau government's foreign policy reflects the continuity of Canadian-Latin American relations since 1867. Trade, investment, communications, education (through missionary efforts), and development have been for a long time objects of major interest in Canadian contact with Latin America. Canada's foreign policy in this region is open to review, and such review does not necessarily lead to expansion. Canada, with its global interests and cultural duality, is likely to focus its attention on a few Latin American nations rather than trying to build relationships with all of them.